THE ANALYSIS OF FACTORS AFFECT INCOME SMOOTHING ON MISCELLANEOUS INDUSTRY COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Anwar, Arfianti Novita; Chandra, Teddy (LLDIKTI Wilayah X, 2017)
The objective of this research is to identify the factors which have influence on income smoothing at Miscellaneous Industry companies listed on Indonesian Stock Exchange period 2009-2013. Independent variables of this research include Return on Asset (ROA), Company Size, Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), and Financial Leverage while the dependent variable is income smoothing. The sample used in this study is 29 Miscellaneous Industry companies listed on the Indonesian Stock Exchange within a period of five years beginning in 2009 until 2013 with the selection method of purposive sampling. To identify the companies doing income smoothing, the Eckel Index was used. Statistical analysis used in this study uses descriptive statistics, multiple linear regressions and discriminant analysis. The results show that partially only company size and dividend payout ratio have significant impact on income smoothing meanwhile Return on Assets, Debt to Equity Ratio, Financial leverage did not show significant influence on income smoothing practices. The result of discriminant analysis shows there is significant difference of Return On Assets between income smoothing and non-smoothing company. Penelitian ini ditujukan untuk mengidentifikasi faktor-faktor yang mempengaruhi perataan laba pada perusahaan aneka industri yang terdaftar di Bursa Efek Indonesia pada periode 2009 – 2013. Variabel bebas yang digunakan dalam penelitian ini mencakup Return on Asset (ROA), Ukuran Perusahaan, Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER) dan Financial Leverage, dengan variabel terikat perataan laba. Perusahaan yang menjadi sampel penelitian terdiri dari 29 perusahaan aneka industri yang dipilih dengan menggunakan metode purposive sampling. Untuk mengidentifikasi perusahaan-perusahaan yang melakukan praktik perataan laba dipergunakan indeks Eckel. Alat analisis yang dipergunakan untuk melakukan analisis deskriptif kuantitatif adalah analisis linear berganda dan analisis diskriminan. Hasil penelitian menunjukkan bahwa seluruh variabel bebas yang dipergunakan mampu menjelaskan proses perataan laba yang dilakukan oleh perusahaan dan yang memiliki pengaruh signifikan adalah ukuran perusahaan dan Dividend Payout Ratio. Sementara hasil dari analisis diksriminan menunjukkan bahwa terdapat perbedaan Return on Asset antara perusahaan yang melakukan praktik perataan laba dengan perusahaan yang tidak melakukan perataanlaba